Comparison of delivery outcomes in nulliparous women in two groups of early and late amniotomy: A Clinical Trial - Ommolbanin Zare; Bita Jamali; Azadeh Kiapour; Maria KarbalaeiZadeh (Mashhad University of Medical Sciences, 2019)
Introduction: Amniotomy is usually used to induce or strengthen labor, and can affect labor progression if it was at suitable time. This study was performed with aim to compare delivery outcomes on nulliparous women in two groups of early and late amniotomy.  Methods: This clinical trial study was performed on 70 nulliparous women referred to Amol medical educational center of Imam Ali Hospital in 2016-2017. Nulliparous women with spontaneous labor were divided into two groups: early amniotomy (≤4 cm) and late amniotomy (>≤4 cm). Data collection tool was a checklist including the characteristics of the research units, the form of partogragraphy and assessment of first, second, third stages of labor and neonate. Individual characteristics, oxytocin infusion, stages of labor and neonatal Apgar score were collected by these tools. Data were analyzed by SPSS software (version 20) and independent t-test and Chi-square test. P<0.05 was considered statistically significant. Results: There was significant difference between two groups in mean duration of first and second stages of labor (p <0.001, p = 0.025, respectively). Duration of first stage of labor was longer in early amniotomy group and duration of second stage was longer in late amniotomy group. However, two groups had no significant difference in mean of duration of third stage of labor (p = 0.078). First and fifth minutes Apgar score of neonates was not significantly different between two groups (p = 1). Conclusion: Although early and late amniotomy had same effect on neonatal outcomes, but late amniotomy (standard) decreased duration of labor in nulliparous women.